POLICE AND POWER IN A PANDEMIC: REFLECTIONS ON THE RISE OF POLICE BRUTALITY DURING COVID- 19 AND ITS IMPLICATIONS ON SOCIAL JUSTICE IN SOUTH AFRICA (The Pretoria Student Law Review, 2021)
The global COVID-19 pandemic came at a time of already increasing police brutality and has since accelerated this nationwide issue. This increasingly frequent behaviour is due to the calling of a state of disaster, the limiting of fundamental rights by force, and the overlooking of essential methods that help to hold the police accountable. This article will critically reflect on the increase in police brutality in South Africa during the initial lockdown period, highlighting how it affects social justice.
Keywords: police brutality; social justice; COVID-19; lockdown